Enhanced charge carrier injection in heterojunction organic field-effect transistor by inserting an MoO3 buffer layer - 于欣格 于军胜 黄伟 曾红娟 (中国物理B：英文版, 2012)
A top-contact organic field-effect transistor （OFET） is fabricated by adopting a pentacene/1,11-bis（di-4- tolylaminophenyl） cyclohexane （TAPC） heterojunction structure and inserting an MoO3 buffer layer between the TAPC organic semiconductor layer and the source/drain electrode. The performances of the heterojunction OFET, including output current, field-effect mobility, and threshed voltage~ are all significantly improved by introducing the MoO3 thin buffer layer. The performance improvement of the modified heterojunction OFET is attributed to a better contact formed at the Au/TAPC interface due to the MoO3 thin buffer layer, thereby leading to a remarkable reduction of the contact resistance at the metal/organic interface.